The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1515/jcim-2019-0209
|View full text |Cite
|
Sign up to set email alerts
|

A prospective controlled study on Ramadan fasting in the healthy young males in summer in Germany: effect on cytokines

Abstract: Short communicationDuring the Ramadan fasting (RF) month, participants restrict some activities during day time, particularly consumption of food and beverages. In Germany, Muslims fast about 18–19 h a day when Ramadan falls in the summer. This longer period of restriction could lead to the changes of the body physiology, anthropometric parameters and biological mediators.ObjectivesThis study aimed to determine the effect of Ramadan fasting on cytokines (Interleukin (IL)-1β. IL-6, IL-8, IL-10, IL-12, tumor nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
2
2
Order By: Relevance
“…In this study, the level of IL-8, particularly compared to T2, was gradually decreasing until T5. This result is different from other studies ( 14 , 15 ). In one study, there was no significant alteration of IL-8 ( 14 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study, the level of IL-8, particularly compared to T2, was gradually decreasing until T5. This result is different from other studies ( 14 , 15 ). In one study, there was no significant alteration of IL-8 ( 14 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This result is different from other studies ( 14 , 15 ). In one study, there was no significant alteration of IL-8 ( 14 ). Meanwhile, in another study, significant alterations were observed ( 15 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the reduction in TNF-α is supported by a previous study, in which it was demonstrated that TNF-α was reduced after Ramadan fasting both at serum and mRNA levels 36 . Moreover, other studies conducted in Germany and the United Arab Emirates (UAE) showed that IL-6 and TNF-α were significantly reduced at the end of Ramadan, while IL-10 was increased but did not reach a significant level in the German study 42 , but it was significantly increased in the UAE study 43 .…”
Section: Discussionmentioning
confidence: 93%